BARRIERS THAT MAKE IT DIFFICULT FOR SMALL-SIZED COMPANIES TO IMPLEMENT ERP SYSTEMS COMPARED TO LARGE-SIZED COMPANIES - Coutinho, Andre Isola; de Souza, Leticia Costa (Revista Interface Tecnológica, 2023)
The article sought to assess the barriers faced by small-sized companies (EPP’s), in the implementation of an ERP system (ERPs - Enterprise Resource Planning) and compare them with those faced by large-sized companies. Its main objective is to raise and evaluate the most common causes in both sizes, so that there is a prior study, and these barriers can be avoided, through the range of benefits that these types of systems add to organizations. For that, through exploratory and descriptive research, studies were carried out, whose results showed that the main barriers found in both sizes are related to the changes and resistance faced by the organizational culture, and that the efficiency of a implementation of ERP systems will depend on your level of planning and not on the size of the company, in addition to a systemic view of administration on the part of managers in understanding the best way to manage processes within this objective.